2021
DOI: 10.1002/jmv.26772
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and genetic diversity of norovirus infection in children with acute gastroenteritis in Bangladesh, 2014–2019

Abstract: Acute gastroenteritis (AGE) is one of the most common diseases in children, and it continues to be a significant cause of morbidity and mortality worldwide. Norovirus is one of the major enteropathogens associated with both sporadic diarrhea and outbreaks of gastroenteritis. This study aims to investigate genotype diversity and molecular epidemiology of norovirus in Bangladesh. A total of 466 fecal specimens were collected from January 2014 to January 2019 from children below 5 years old with AGE in Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
7
8
0
Order By: Relevance
“…In humans, previous studies have reported a prevalence of 9.9% in Karachi alone, and 16.1% and 19.5% in studies conducted in multiple cities ( 8 , 24 , 29 ). Prevalence data reported in this study falls in the range of other studies conducted in similar settings such as 10.3% in India ( 30 ), 5.1% in Bangladesh ( 31 ), 11.2% in Taiwan ( 32 ), and 10% in Yemen ( 33 ). Many of the previous studies tested the GI and GII genogroups but in this study, we have only tested samples for the GII genogroup which is the most prevalent genogroup in humans at the global level including Pakistan ( 8 , 31 , 34 , 35 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In humans, previous studies have reported a prevalence of 9.9% in Karachi alone, and 16.1% and 19.5% in studies conducted in multiple cities ( 8 , 24 , 29 ). Prevalence data reported in this study falls in the range of other studies conducted in similar settings such as 10.3% in India ( 30 ), 5.1% in Bangladesh ( 31 ), 11.2% in Taiwan ( 32 ), and 10% in Yemen ( 33 ). Many of the previous studies tested the GI and GII genogroups but in this study, we have only tested samples for the GII genogroup which is the most prevalent genogroup in humans at the global level including Pakistan ( 8 , 31 , 34 , 35 ).…”
Section: Discussionsupporting
confidence: 63%
“…Prevalence data reported in this study falls in the range of other studies conducted in similar settings such as 10.3% in India ( 30 ), 5.1% in Bangladesh ( 31 ), 11.2% in Taiwan ( 32 ), and 10% in Yemen ( 33 ). Many of the previous studies tested the GI and GII genogroups but in this study, we have only tested samples for the GII genogroup which is the most prevalent genogroup in humans at the global level including Pakistan ( 8 , 31 , 34 , 35 ). A study conducted in the neighboring country, India, reported 82.5% of cases of genogroup GII as compared to 12.5% of cases for the GI genogroup ( 30 ).…”
Section: Discussionsupporting
confidence: 63%
“…Genogroups GI, GII, and GIV can infect humans. In the past decades, GII.4 NoVs have been the most predominant strain worldwide, accounting for 70–80% of all reported outbreaks ( de Graaf et al, 2016 ; Dey et al, 2021 ). Meanwhile, the novel GII.P17-GII.17 NoVs strain became the predominant strain, surpassing the GII.4 strain, in Asia during the 2014–2016 NoV epidemic seasons ( de Graaf et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, these criteria are adopted in the current consensus, with the addition of an age cut-off of 6 months. Viral AGE most often occurs in younger age groups [ 33 , 34 ], who are more susceptible to diseases. Moreover, children below the age of 6 months often benefit through breastfeeding from the protective effect of maternal antibodies, which also protect against viral pathogens [ 35 ].…”
Section: Diagnostic Workupmentioning
confidence: 99%